Impact Assessment of integrated Pest Management modules validated for Brinjal, Paddy, Pigeon pea and Cauliflower - Das, Niranjan; Giri, B.P.; Das, A.B. (Journal of Agricultural Extension Management, 2018)
Impact assessment of IPM modules validated by KVK, Boudh, Odisha during 2009-2012 revealed that the technologies are being adopted by the farmers at variable rate over time. The highest adoption rate (45%) was observed in IPM module for management of fruit and shoot borer infestation in brinjal, with horizontal expansion of 115 ha additional area over four years. Lower adoption rate (20%) was observed for the IPM module for management of pod borer in pigeon pea. The IPM modules for management of stem borer in paddy and tobacco caterpillar in cauliflower were adopted by 25% and 30% respondents respectively. Among the biological constraints, non-availability of pheromone trap, lure and bio agents rank first with frequency of 80% followed by delay/difficulty in input availability (76%). The other deterrents observed under this category are non-availability of neem oil/cake, inadequate supply and poor quality of inputs. Among technological impediments are non-availability of skilled labour which ranks first (75%) followed by lack of trained extension personnel for follow-up action. High cost of labour is the major socio economic constraint (90%) followed by lack of credit facility (82%) for adoption of these technologies. For successful adoption of these modules in a sustainable manner it is essential to address these constraints in a time bound manner and system paradigm mode.